A GIS-AHP based approach for optimization of quarry site location around Harer and Dire-Dawa towns, Eastern Ethiopia - Gudissa, Leta; Raghuvanshi, Tarun Kumar; Meten, Matebie; Chemeda, Yadeta C. (Journal of Environmental Engineering and Landscape Management, 2022)
The problem of environmental degradation and pollution resulting from quarry operations is becoming a critical problem. Therefore, the selection of optimal quarry sites is a prerequisite for safe operation and economic viability. The present study was carried out around Harer and Dire-Dawa towns to identify the optimal location of quarry sites by using an integrated AHP and GIS approaches. The selection was carried out by considering environmental and socio-economic factors. For each of the factors, appropriate classifications and criteria were formulated. Finally, a weighted overlay analysis was applied to produce the preliminary quarry site suitability map. About 136 km2 of the area is highly suitable, 1,587 km2 is moderately suitable, and 2,166 km2 has low suitability for quarry site. The approach followed by the study helped to narrow the area to the suitable sites that may further be studied through detailed field investigation. Hence, it can be adopted elsewhere as a guide for economical quarry site selection.